Pancasila Education in the Midst of Globalization: Maintaining Modern Identity and Values - Gibran, Muhammad Daffa; Dwi Suwarno, Sundi Puspaning Arum; Putri, Fadiyah Eka; Saputra, Eggy; Bustami, Daliya; Sari, Ramona Jovita; Felisa, Hazzela Atlica (Jurnal Edukasi Terkini, 2025)
Purpose-This article aims to discuss various efforts that can be made to maintain the existence of Pancasila and its relevance in everyday life in the era of globalization. The main focus is how the values ​​of Pancasila can remain alive and applied amidst the flow of modernization and the influence of foreign cultures.Research Methodology / Design / Approach- The method used in this article is a literature review. This approach involves a study of various studies and literature that highlight the importance of internalizing Pancasila values ​​through education, public policy, and the active role of government institutions and society.Findings -The findings show that although globalization brings strong influences from foreign cultures and values, Pancasila can still be maintained and strengthened through a continuing education approach, the cultivation of national values, and policies that support the strengthening of these values. This confirms that Pancasila remains relevant as an ideological and moral guideline for the Indonesian nation.Originality / Value -This article makes an important contribution by emphasizing that the existence of Pancasila as the foundation of the identity and integrity of the Indonesian nation must not only be understood conceptually but must also be implemented in real life. Collective efforts from all elements of society are the main key to ensuring that the values ​​of Pancasila continue to live amidst the challenges of globalization.